To study the fast food consumption trends in India - Lakra, Rakshit; Singh, Priyanka (Universal Research Reports, 2023)
India may take a holistic approach to studying the fast food industry by looking at the industry as a whole. Understanding the trends, causes, and repercussions of fast food consumption in India is the goal of this study. Quantitative and qualitative approaches may both be used in the investigation. Quantitatively, surveys and questionnaires may be issued to a cross-section of the Indian population to learn more about their fast food habits, tastes, and demographics. Current consumption statistics and sales records from fast food businesses may provide light on industry tendencies via analysis. The underlying reasons and cultural factors that affect fast food choices in India may be uncovered using qualitative methods such as in-depth interviews and focus groups. The social, economic, and lifestyle elements at play may be better understood with the use of this qualitative information. Since eating habits and preferences may vary greatly from one Indian state or city to the next, it is essential to look at regional differences. The ever-changing nature of the fast food industry may be better understood by looking at how various chains have adapted their menus to meet consumer demand in different regions. Research on the effects of rising fast food consumption in India should look at more than just the weight gain and illness risks that come with it.